Diversity of Macromoths (Lepidoptera: Heterocera) in the Poring Hill Dipterocarp Forest, Sabah, Borneo - Fatimah, Abang; Catherine, Karim (Elsevier, 2005)
The diversity and abundance of the macromoths were investigated in a hill dipterocarp forest, Poring, Sabah, using modified Pennsylvanian light traps conducted bimonthly for a total of 24 nights from March through December 1999. The light-traps were set for five continuous nights for every two months during the study period. A total of 1, 169 species from 9, 624 individuals and 15 families of the macromoths were recorded. The overall species diversity index for the macromoths was found to be extremely high (348.56 ± 12.56 (95% confidence range)). The hill dipterocarp forest at Poring was characterized by the dominance of Noctuidae and Geometridae and the presence of the single species of the Bornean Brahmaeidae and five rarely encountered species of Saturniidae. The results of this study show that most common species in Poring are Asura sp. (Arctiidae: Lithosiinae), Chamaita trichopteroides Walker (Arctiidae: Lithosiinae), Asura bizonoides Walker (Arctiidae: Lithosiinae) and Heterostegane warreni Prout (Geometridae: Ennominae. These species could be considered as characteristic of the hill dipterocarp macromoth fauna. Twenty-five percent of the total species collected (298 species) are considered as rare species, being represented by single individuals, or singletons. These singletons were highly represented in the Geometridae (33%), followed by Noctuidae (24%) and Lymantriidae (11%). Species diversity of the macromoth in Poring is further discussed.